Genesis and new mineral chemistry data of carlosbarbosaite, a potential U and Nb ore source from miarolitic-, A-type granites and NYF pegmatites of the La Chinchilla pluton, Velasco ranges, La Rioja, Argentina - Lira, Raul (2023)
The La Chinchilla granite is a ~3.75 km2 epizonal pluton of Lower Carboniferous age located in Sierra de Velasco, Sierras Pampeanas, Argentina. Equigranular micropegmatitic and porphyritic main granite types host abundant millimeter-, to < 2 m-sized miarolitic pegmatites and pockets of simple major mineralogy (± beryl). Both granite types host micrometer sized accessory species [i.e., monazite-(Ce), several high field strength element oxide species, ilmenite, cassiterite, fluorapatite] and fluorite. A F-Na rich fluid phase promoted strong albitization at late miarolitic stages, along with crystallization of extremely F-rich polylithionite and fluorite, and the formation of replacing pyrochlore group species associated with a second generation of cassiterite. The increase of the Ta# from hydroxycalciopyrochlore to hydroxycalciomicrolite and from micromiarolitic cassiterite (cassiterite 1) to hydrothermal cassiterite (cassiterite 2), supports Nb-Ta fractionation at hydrothermal temperatures. Carlosbarbosaite [(UO2)2Nb2O6(OH)2•2H2O] occurs as a pseudomorphic or as a short-range transported phase. Indigenous carlosbarbosaite formed after columbite-(Fe), U-free Nb-bearing ilmenite and likely after U-bearing pyrochlore supergroup species and a columbite group mineral, plausibly due to interaction with a hydrothermal-, U6+(±Nb±Ta)-enriched fluid, in some cases a SiO2-bearing fluid. This fluid likely represents a lower temperature, less alkaline and more oxidizing fluid that evolved from the higher temperature F-Na-rich fluids active during the late-miarolitic hydrothermal stage. Indigenous carlosbarbosaite has the ideal U-, Nb-rich endmember composition, though is significantly richer in Ca and poorer in total Nb+Ta but with higher Nb# than the one from the type locality. Supergene fluids deposited the transported type which attained economic concentrations in a fault zone where restricted-, likely alkaline oxidizing-conditions could have favored Nb mobility.